2018
DOI: 10.1016/j.bjm.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A practical molecular identification of nonfermenting Gram-negative bacteria from cystic fibrosis

Abstract: Identification of nonfermenting Gram-negative bacteria (NFGNB) of cystic fibrosis patients is hard and misidentification could affect clinical outcome. This study aimed to propose a scheme using polymerase chain reaction to identify NFGNB. This scheme leads to reliable identification within 3 days in an economically viable manner when compared to other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Similarly, other common CF pathogens encode l -lactate dehydrogenases homologous to LldD and LldA. Using the P. aeruginosa PA14 LldD, LldA, and LldE protein sequences, we searched for homologues in representative strains of Achromobacter xylosoxidans , Burkholderia multivorans , Haemophilus influenzae , and Stenotrophomonas maltophilia ( 33 35 ). We found that H. influenzae and S. maltophilia contain an l -lactate dehydrogenase homolog but that A. xylosoxidans and B. multivorans , like P. aeruginosa , contain multiple homologs.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, other common CF pathogens encode l -lactate dehydrogenases homologous to LldD and LldA. Using the P. aeruginosa PA14 LldD, LldA, and LldE protein sequences, we searched for homologues in representative strains of Achromobacter xylosoxidans , Burkholderia multivorans , Haemophilus influenzae , and Stenotrophomonas maltophilia ( 33 35 ). We found that H. influenzae and S. maltophilia contain an l -lactate dehydrogenase homolog but that A. xylosoxidans and B. multivorans , like P. aeruginosa , contain multiple homologs.…”
Section: Resultsmentioning
confidence: 99%